2021
DOI: 10.5812/semj.112681
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anti-SARS-CoV-2 Antibody in Hospital Staff in Double-Center Setting: A Preliminary Report of a Cohort Study From Iran

Abstract: Background: The outbreak of COVID-19 in China in late 2019 was an unprecedented catastrophe that also involved many other countries, including Iran. Concerning the danger of disease contagion, it is necessary to detect asymptomatic or mild cases, especially in hospital staff who are highly exposed to the disease. Objectives: In this serosurvey study, we aimed to estimate IgG seroprevalence among hospital staff in two public hospitals to determine local transmission and infection risk factors, as well as protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In line with our recent studies on COVID-19 (11)(12)(13) and to help diagnose SARS-CoV-2, this study summarizes the methods used to identify coronavirus nucleic acid and examines the effectiveness of coronavirus nucleic acid detection kits as well as the performance of other diagnostic techniques. It is hoped that the findings would help researchers and physicians develop better techniques for the timely and effective diagnosis of coronavirus infections.…”
Section: Contextmentioning
confidence: 90%
See 2 more Smart Citations
“…In line with our recent studies on COVID-19 (11)(12)(13) and to help diagnose SARS-CoV-2, this study summarizes the methods used to identify coronavirus nucleic acid and examines the effectiveness of coronavirus nucleic acid detection kits as well as the performance of other diagnostic techniques. It is hoped that the findings would help researchers and physicians develop better techniques for the timely and effective diagnosis of coronavirus infections.…”
Section: Contextmentioning
confidence: 90%
“…In our previous study measuring the IgG level of COVID-19 using the ELISA technique, it was revealed that there was anti-SARS-CoV-2 IgG in the blood of 29 patients, and that a majority of individuals did not have anti-SARS-CoV-2 IgG. Accordingly, education and technical advice on COVID-19 is necessary (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fever, cough, fatigue, shortness of breath, and loss of smell and taste are the common main symptoms of the disease. The range of COVID-19 manifestations varies from asymptomatic infection to acute respiratory infection (4)(5)(6). For instance, previous studies have suggested that approximately 81% of patients with novel coronavirus infection are mild cases, 14% of the cases develop the severe disease requiring hospitalization and oxygen therapy, and 5% of the cases require admission to an intensive care unit (ICU) (5,7).…”
Section: Introductionmentioning
confidence: 99%
“…Health personnel and more specifically hospital workers are highly exposed to the virus and therefore at higher risk for infection. [ 17 ] In this respect, front-line clinicians need to be educated for offering care for COVID-19 as with other critical situations such as large-scale catastrophes and pandemics. [ 18 ] In addition, students (specifically medical students) should be mentored and supported in order to mentally and emotionally deal with additional stress related to the pandemic.…”
Section: Introductionmentioning
confidence: 99%